Effectiveness of simplified diabetes nutrition education on glycemic control, and other diabetes-related outcomes in patients with type 2 diabetes mellitus in Basrah, Iraq - Hashim, Almaliki Saman Agad (2020)
Type 2 Diabetes (T2DM) is a global public health concern, with the majority of the patients had inadequate glycemic control. In Basrah, Iraq, one of the factors affecting glycemic control is low health literacy (HL) level. T2DM patients with low HL have limited ability to understand and apply the regimen to their diabetes self-management. Therefore, a simplified diabetes nutrition education (SDNE) may be required to ensure optimum diabetes care. This study evaluates the effectiveness of SDNE on glycemic control and other diabetes-related outcomes in patients with T2DM in Basrah, Iraq. This study involved three phases based on the Generalized Model for Program Planning conducted at Faiha Specialized Diabetes, Endocrine, and Metabolism Centre (FDEMC), in Basrah, Iraq. Phase I was a cross-sectional study that included 280 participants in determining the factors associated with glycemic control. The factors included socio-demographic status, medical characteristics, nutritional status, lifestyle behavior, and HL level. The results from Phase I informed the content for the Phase II study, which involved developing and assessing nutrition education materials. The developed nutrition education materials were assessed for face validity, readability, and acceptability using a 14-item HL Scale and the Suitability Assessment of Materials (SAM) instrument in 30 participants with T2DM. The experts validated the content of the materials. The effectiveness of the developed nutrition education materials named SDNE was evaluated at Phase III using a randomized controlled trial (RCT) on glycemic control and other diabetes-related outcomes for 22 weeks in patients with T2DM (n = 208). The assessments were performed at baseline (T0), at 12-week of intervention (T1), and at 10-week of follow-up (T2). 208 participants were randomly allocated to either the nutrition education group (NEG, n = 104), or the control group (CG, n = 104). Those in the NEG received the SDNE curriculum for 12 weeks (12 weekly classes, 1 to 1.5 hours each). Participants in the CG continued with the usual care. At Phase I, the participants (N = 151) were at their 50s' with the HbA1c, and HL scores were 10.0 ± 2.6% and 45.7 ± 24.6. The majority of the participants (76.4%) had either inadequate (55.7%) or marginal HL (20.7%). Factors associated with glycemic control included low HL score, low total income, selfemployed, multiple treatments (oral anti-diabetic drugs and insulin therapy), low physical activity level, presence of comorbidities, and low vegetable intake. All of the factors explained 35% of the total variation in HbA1c (adjusted R2 = 0.35; p = 0.005). The modifiable nutrition-related factors that were associated with glycemic control (i.e., HL levels, physical activity, and vegetable intakes) were considered the key nutrition component in the development of nutrition education materials at Phase II. The SDNE curriculum emphasizes the use of the Plate Method and "eating vegetables before carbohydrates." The developed SDNE had the HL scale score of 57.1, indicating it was readable and acceptable among participants. The SAM instruments score was 34 out of 40, indicating the SDNE curriculum’s suitability. The dietitians and an endocrinologist confirmed the content validity of the SDNE. At Phase III, a total of 208 patients aged 20-64 years old with a confirmed diagnosis of T2DM participated in the study. At 22 weeks, the interaction effects were significant and more pronounced in NEG than CG for HbA1c (p < 0.001) and other diabetes-related outcomes including on total cholesterol (p = 0.001), low-density lipoprotein (p = 0.009), high-density lipoprotein (p < 0.001), triglyceride (p = 0.01), waist circumference (p < 0.001), BMI (p = 0.008), total energy (p < 0.001), carbohydrate (p < 0.001), and vegetable (p < 0.001) intakes. Health belief model (HBM) constructs (p = 0.003), diabetes knowledge (DK) (p = 0.004), and HL score (p < 0.001) were also improved. In conclusion, patients with T2DM in Iraq had poor glycemic status, low HL, low vegetable intake, and decreased levels of physical activity. These components were included in the development of a simplified and visual educational material called SDNE. SDNE was demonstrated to be effective in improving HbA1c, metabolic parameters, dietary intake, and physical activity. Likewise, HBM, DK, and HL. SDNE can be used in Clinics as simplified pictorial leaflets that will assist nutritionists in providing appropriate and accessible nutritional education to patients with T2DM.